The Weird Sisters and the Circean Myth of Femininity in Geoffrey Wright’s Macbeth/Las brujas, Circe y el mito de la feminidad en el Macbeth de Geoffrey Wright - Marino-Faza, Maria (The Grove - Working Papers on English Studies, 2016)
One of the typical figures used to construct monstrosity in terms of gender is that of the witch and, probably, one of the best well-known portrayals of these women appears in Shakespeare’s Macbeth. Written at the beginning of the seventeenth-century, soon after James I became king of England, this theatre play echoes contemporary beliefs on witchcraft and portrays the weird sisters as the characters that set in motion all the events in the play. The witch is understood as an abject figure and gender becomes a key element in this construction of monstrosity. Accordingly, Geoffrey Wright’s adaptation to the screen, uses the mythological figure of Circe as a basis for this contemporary representation of femininity, stressing not only witches’ threatening potential but also the danger their highly erotized nature poses.